Integration of Arthrospira platensis (spirulina) into the brewing process to develop new beers with unique sensory properties - Beisler, Nino; Sandmann, Michael (Frontiers in Sustainable Food Systems, 2022)
Microalgae, and particularly the cyanobacterium Arthrospira platensis (spirulina), have attracted much attention due to their wide range of uses. The potential use of spirulina in food is mainly driven by its high content of macro and micronutrients including proteins, γ-linolenic acid, sulfated polysaccharides, minerals, vitamins, and the natural pigment phycocyanin. Despite these potential benefits, spirulina is still not widely used in the food industry due to numerous technological challenges during manufacturing or specific sensory issues in the final product. This research deals with the feasibility of integrating spirulina into the brewing process to create a tasty beer with high consumer acceptance. In the novel recipes, 5% (w/w) of the malt was replaced by spirulina powder. The first part of the study investigated inclusion at different time points throughout manufacturing of a reference beer style (mild pale ale). Compared to the control, alcoholic fermentation was slightly influenced by cyanobacterial biomass but resulted in a beer with a typical beer-like character. Sensory evaluations including a simple descriptive test, a popularity analysis, and Just-About-Right-Questions, indicated a complex alteration in the sensory properties. This includes a dominant algal taste that disturbs the character of the pale ale beers but also a deep blue color of the beer, if spirulina was included during the wort cooling phase. Based on these results, another set of beers with a higher original extract concentration and increased hop dosages was produced. These beers had a high popularity (6.0 original TESTSCORE; 7.12 and 6.64 optimized TESTSCORE), and also exhibited a deep blue color due to the natural pigment phycocyanin from spirulina. Further, bitterness and algal taste was rated by most of the panelists to be “just right” and the simple descriptive test indicated “sweetness” as important attribute which was not expected for this hoppy beer style.